Evaluating, Screening and Selecting Yardlong Bean [Vigna unguiculata subsp. sesquipedalis (L.) Verdc.] for Resistance to Common Cutworm (Spodoptera litura Fabricius) - Tianchi Yao; Yufei Xu; Huiyan Jiang; Xinxin Chen; Xiaofeng Liu; Huatao Chen; Hongmei Zhang; Guangnan Xing (Agronomy, 2023)
The yardlong bean [Vigna unguiculata subsp. sesquipedalis (L.) Verdc.] is an important vegetable crop, but it is prone to pest infestation. Therefore, breeding insect-resistant varieties is essential to reduce pesticide applications and to increase bean quality and yield. In the present study, 64 yardlong bean varieties were screened for their resistance to the common cutworm (Spodoptera litura Fabricius). In the greenhouse, leaves, pods, and seeds of yardlong beans were harmed by naturally occurring common cutworms. Seventeen insect-resistant and four insect-susceptible yardlong bean varieties were identified based on the weight of the nine-day-old larvae and 72 h weight increases of 4th instar larvae through feeding newly hatched and 4th instar larvae, respectively. Subsequent verification feeding experiments with newly hatched larvae showed that Zhuzaidou and Pingtangjiangdou’s insect resistance are the weakest and Jiangdou No.5, j-1, Zhijiangtezao No. 30, and Changcaidou have the strongest insect resistance. In 21 yardlong bean varieties, starch content and larval weight showed negative correlation and there was positive correlation between crude protein and larval weight, but almost neither of them reached significant levels. Through organ antibiotic and antixenotic experiments, it was concluded that common cutworms preferred feeding on yardlong bean leaves, and the weight increase of common cutworms feeding on leaves was higher than that of pods and seeds. These insect-resistant yardlong bean varieties warrant further investigation in basic antibiosis mechanism research in yardlong beans and can serve as germplasm resources for breeding programs engaged in reducing pesticide usage.